Extracurricular Activities in English for Students in Facing The Industrial Revolution 4.0 - Satriani; Razaq, Yusuf; Amiruddin; Munawir, Ahmad; Hasbi, Muhammad (Education and Talent Development Center of Indonesia, 2022)
Teaching English to elementary school students (SD) was created as an extracurricular activity. However, impediments such as instructor capacity or aptitude, as well as school conditions, can demotivate children from learning English. This community service project (PKM) seeks to provide English language help to elementary school children in Wajo Regency in their extracurricular English learning. The goal of the project is to develop a fun and fascinating English teaching and learning process and method at Wajo Inpres Elementary School through online tools like Zoom, WhatsApp Group, and Google Classroom (impact of the COVID-19 pandemic). Pammana Subdistrict, Wajo Regency, was very successful or experienced an increase, particularly in speaking and listening, as evidenced by the results of the pre-test listening (53.87 percent) and speaking (55.32 percent) after doing the post-test. Increased listening (81.6 percent) and speaking (55.32 percent) after doing the post-test (82.3 percent).